The Make-Believe Space : Affective Geography in a Postwar Polity - Navaro-Yashin, Yael, 1969- (Book collections on Project MUSE., 2012)
This is an anthropological look at the Turkish territory of Northern Cyprus, a self-defined state, which is actually imaginary (because it is only recognized by Turkey). Navaro-Yashin surveys the affective landscape, examining the sense of haunted property and objects lost and gained in the partition, along with people s relation to the fictive remapping of places and history by this new state.